Pensions, Income Taxes and Homeownership: A Cross-Country Analysis - Hans Fehr; Maurice Hofmann; George Kudrna (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper studies the role of pensions and income taxes in determining homeownership and household wealth. It provides a cross-country analysis, using tax and pension policy designs in Germany, the US and Australia. These developed nations have similar incomes per capita but very different homeownership rates, with the US and Australia having much higher homeownership compared to Germany. The question is to what extent the observed differences in homeownership are induced by national tax and transfer policies. To that end, we develop a stochastic, overlapping generations (OLG) model with tenure choice. The model is calibrated to Germany featuring German statutory public pension and dual income tax systems, and then applied to study the effects of alternative income tax and pension policy structures. Our simulation results indicate that the US and Australian policy designs have a dramatic impact on homeownership, explaining more than half of the observed differentials. We also show significant macroeconomic effects due to differences in tax and pension policies.
Keywords: R21; H55; H31; H24; C68; 330; housing demand; social security; income taxation; stochastic general equilibrium